2022
DOI: 10.1136/jcp-2022-208583
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and genetic analyses of pulmonary enteric adenocarcinoma

Abstract: AimsPulmonary enteric adenocarcinoma (PEAC) is a rare variant of pulmonary adenocarcinoma. Due to its rarity, few pathological and molecular studies have been performed on PEAC. We herein conducted clinicopathological, immunohistochemical and molecular analyses of PEAC with a focus on its differentiation from invasive mucinous adenocarcinoma (IMA).MethodsWe examined the clinicopathological features of 16 cases of PEAC and performed a genetic analysis using next-generation sequencing (NGS). The results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The overall PEAC prevalence accounts for 0.5% of all NSCLC cases [ 12 , 13 ]. The age of presentation is generally between 50 and 60 years and patients usually present more advanced disease at diagnosis compared to those affected by CLA, although some cases with early-stage disease have been described [ 14 ].…”
Section: Pulmonary Enteric Adenocarcinomamentioning
confidence: 99%
See 3 more Smart Citations
“…The overall PEAC prevalence accounts for 0.5% of all NSCLC cases [ 12 , 13 ]. The age of presentation is generally between 50 and 60 years and patients usually present more advanced disease at diagnosis compared to those affected by CLA, although some cases with early-stage disease have been described [ 14 ].…”
Section: Pulmonary Enteric Adenocarcinomamentioning
confidence: 99%
“…The first hypothesis, as put forward by Satoh et al [ 17 ], is based on the presence of common cancer stem cells in the lower respiratory tract and gastrointestinal mucosa, including goblet cells, Paneth cells and neuroendocrine cells. The role of smoking is still controversial [ 15 , 17 ], with some studies showing no differences in terms of smoking status between PEAC and primary lung adenocarcinoma [ 12 , 13 ].…”
Section: Pulmonary Enteric Adenocarcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified smoking as a predisposing factor for PEAC, and the WNT-SOX2 signaling regulation pathway is over-activated under the stimulation of smoking and other factors, which may lead to intestinal metaplasia of airway basal cells. However, a recent study suggested that smoking may not be an important risk factor for the development of PEAC ( 23 ). In addition, several studies have shown that males are more likely to have PEAC, while other studies have come to the opposite conclusion ( 24 ).…”
Section: Discussionmentioning
confidence: 99%